Ukrainian Council of Churches and Religious Organizations as a Voice for Justice and Humanity during the Russian Invasion - Vasin, Maksym (Review of ecumenical studies, 2023)
The Russian invasion of Ukraine in February 2022 has prompted a critical examination of the church’s role as a social institution during times of war. During such circumstances, national and global religious leaders are typically expected to spearhead peacebuilding initiatives focused on saving civilians, protecting critical infrastructure, and mitigating the potential for widespread destruction and humanitarian crises. In this case, however, the Kremlin has actively used the Russian Orthodox Church as well as an array of religious figures to justify Russian aggression and legitimize actions that amount to genocide against the Ukrainian people. In contrast, the Ukrainian Council of Churches and Religious Organizations has assumed the role of a moral guide during the war by condemning, with remarkably unity, Russian war crimes and the destructive ideology of Russkiy mir (the Russian world), and instead advocating for a humane approach and proposing peacebuilding initiatives. This paper details the scope and character of the Council’s activities carried out in wartime, providing numerous illustrative examples.